An intelligent algorithm to reduce and eliminate coverage holes in the mobile network - Al-Hashemy Rageed Hussein Hussan (De Gruyter, 2021)
The need for services in the world of telecommunications and the prosperity and rapid development of this sector around the world has led mobile phone companies to compete to provide the best services to customers. One of these devices used for communications is the mobile phone. The mobile phone is simply an electronic device that is mainly serving unwired telecommunications through a cellular network of particular base stations known as cell sites. There are many obstacles or problems in the telecommunication field, and the relevant institutions and companies should find solutions to these obstacles and problems. One of these obstacles in telecommunications is the coverage holes. Coverage holes occur when the location of the mobile phone is set in midway between the two base transceiver stations (BTSs). This causes an abnormal interruption in communication until the user crosses the coverage holes area. This paper presents an intelligent algorithm as a set of technical steps that can be used to improve the communication services of the mobile phone network and to solve the communication problems via the reduction of the coverage holes between two BTSs. It suggests a method that could alleviate this problem using a strategy that reduces the coverage holes by developing an intelligent algorithm system to receive signal strength indicators and use AT command “+CREG” to disconnect and reconnect to available BTS within an acceptable energy level. As a result, the connection turned from marginal into good connection.